Error Analysis of NC-BFSK for Cooperative Diversity with Correlated Links - Swaminathan, Ramabadran (2017)
Cooperative communication plays a vital role in improving the error performance and throughput of a communication system. In this paper, we consider a cooperative diversity system with a source (S), a relay (R) and a destination (D). The major contribution of this paper is two fold: (1) closed form symbol error probability (SEP) expression has been derived considering noncoherent binary frequency-shift keying (NC-BFSK) modulation scheme for cooperative selection diversity system over dependent and identical Nakagami-m fading channels assuming correlation between all possible fading factors and (2) based on the derived end-to-end average SEP expression, performance analysis has been carried out for various special cases assuming decode and forward (DF) protocol at the relay node. Monte Carlo simulations are also performed to validate the derived SEP expression.